Fatwa Majelis Ulama Indonesia Nomor 1 Tahun 2004 tentang Bunga Bank - Sandi Saputra; Selviani Selviani (STAI Auliaurrasyidin Tembilahan, 2021)
This study aimed to explain the citizen of Pulau Palas's perspective on the MUI fatwa number 1 of 2004 regarding bank interest. This type of research was qualitative research using a purposive sampling technique. Data were analyzed using the Miles and Huberman method. The research findings showed that the public agreed that bank interest is usury, the fatwa should be comprehended as long as the decision is sincere for the benefit of the people. However, most of them still rely on conventional banking because of distrust of the system used by Islamic banks, as well as the ignorance of the existence of the fatwa. Therefore, the people viewed that the fatwa was issued to promote or increase the prestige of Islamic banks so that people turn to Islamic banks and leave conventional banks.